Differences in the replicative capacities of clinical isolates of dengue virus in C6/36 cells and in urban populations of Aedes aegypti from Colombia, South America. (2023)
Dengue, the most prevalent arboviral disease worldwide, is caused by any of the four dengue virus (DENV) serotypes that co-circulate constantly in hyperendemic areas such as Medellin (Colombia), and these serotypes are transmitted by mosquitoes of the genus Aedes. In this study, we evaluated the replicative capacity of strains isolated in Medellin between 2003 and 2007 in C6/36 cells and in colonies of Aedes aegypti collected during 2010-2011 from high or low-incidence areas within the same city. The phylogenetic analysis grouped isolates according to the predominant genotypes found in the Americas, and the in vitro characterization showed differences in the morphological changes induced by the isolates of each of the isolated serotypes compared to the reference serotypes. In vitro replicative capacity studies demonstrated that genomic copy number increased at four days post-infection and that cell viability decreased significantly compared to the control for all serotypes. The largest number of genomic copies in C6/36 was produced by DENV-2, followed by DENV-1 and DENV-4; DENV-3 produced the smallest number of genomic copies and had the smallest negative effect on cell viability. Finally, differences in the in vivo replication of intercolonial serotypes between the Rockefeller colony and the field colonies and among the intracolonial serotypes were found. The replication of DENV-2 at 7 and 14 days in both high- and low-incidence colonies was higher than that of the other serotypes, and replication of DENV-3 in the mosquito colonies was the most stable on the days evaluated. Our results support the notion that replication and, possibly, DENV transmission and severity depend on many factors, including serotype and vector characteristics.